Interview with Maria de Nazareth Baudel Wanderley: Teaching rural issues as an essential theme for Brazilian society (PerCursos, 2025)
Maria de Nazareth Baudel Wanderley, PhD in Sociology from the University of Paris With more than 40 years of academic career, she was a professor of Social Sciences at the State University of Campinas and the Federal University of Pernambuco.